2009
DOI: 10.1645/ge-1600.1
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Anisakis simplex Larval Products on the Early and Late Components in the Classical Complement Pathway

Abstract: In previous studies, we have reported that the larval products (crude extract [CE] and excretory-secretory [ES]) of Anisakis simplex showed a dose-dependent inhibition of the lysis mediated by classical (CP) and alternative pathways (AP) of the human complement system, with the major inhibition on the CP rather than on AP. This inhibition of hemolysis is due to the consumption of complement factors because the assays performed shortening the preincubation period result in a significant decrease of the inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In this framework, could be postulated that the higher parasitic burden, the more efficient seems to be the parasite-related manipulation [14,18]. Acting as immune manipulators during infection, parasitic allergens and their cytokines can induce the IgE synthesis or at least the IgG4 one, to avoid the antiparasitic role of complement system [14,25,[34][35][36]. On the other hand, urticaria induction due to IgE-mediated mast cell degranulation seems to be an active parasitic effect that can provide the parasitic migration into tissues [42,43,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this framework, could be postulated that the higher parasitic burden, the more efficient seems to be the parasite-related manipulation [14,18]. Acting as immune manipulators during infection, parasitic allergens and their cytokines can induce the IgE synthesis or at least the IgG4 one, to avoid the antiparasitic role of complement system [14,25,[34][35][36]. On the other hand, urticaria induction due to IgE-mediated mast cell degranulation seems to be an active parasitic effect that can provide the parasitic migration into tissues [42,43,73].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the complement inhibition in humans, the larval L3 products of anisakis exercised a stronger effect on the classical pathway than on the alternative one, constituting a mechanism to evade host defenses, similarly to other parasitic diseases. Detailed studies revealed that larval products of Anisakis simplex act at the level of the C3 and C2 proteins, which are early components of the classical complement pathway [35,36]. In contrast, the asymptomatic infections of human lymphatic filariasis and onchocerciasis are characterized by high plasma concentrations of IgG4 (compared with those of IgE) and of the complement-fixing antibodies IgG1, IgG2 and IgG3 [25].…”
Section: Host-parasite Interaction and Parasito-sis-urticaria Relatiomentioning
confidence: 99%
“…Regarding the complement inhibition in humans, the larval L3 products of anisakis exercised a stronger effect on the classical pathway than on the alternative one, constituting a mechanism to evade host defenses, similarly to other parasitic diseases. In this context, detailed studies revealed that larval products of Anisakis simplex act at the level of the C3 and C2 proteins, which are early components of the classical complement pathway [37, 38]. These findings suggest that parasites cannot "switch off" the humoral host immunity, but they could induce the Th2 profile.…”
Section: The Role Of Host-parasite Interaction In the Relationship Pamentioning
confidence: 99%
“…In this previous work, a possible activation of the complement by incubating appropriate sera dilutions with A. simplex CE and ES concentrations for 0 and 15 min was studied (García-Hernández et al, 2007). When the assays were performed using C5-, C6-, C7-, C8-and C9-deficient sera, A. simplex larval products had no impact on the complement system, whereas CE and ES products influenced the C2 complement component (García-Hernández et al, 2009). AP and CP activities were determined using a modified version of the microassay described previously (Halkes et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings on the activity of A. simplex larval products on the complement system led us to examine a possible interference with various components of the complement cascade (García-Hernández et al , 2007). When the assays were performed using C5-, C6-, C7-, C8- and C9-deficient sera, A. simplex larval products had no impact on the complement system, whereas CE and ES products influenced the C2 complement component (García-Hernández et al , 2009). In this case, among early complement components, A. simplex larval products only produced a dose-dependent inhibition of lysis when C2-deficient serum was tested.…”
Section: Introductionmentioning
confidence: 99%